Teddy bear, teddy bear - Moroney, Tracey (Five Mile ; Manning Partnership [distributor] Rowville, Vic., Bath, 2008)
This enchanting series of 3D board books features the beautiful illustrative artwork of Trace Moroney. With rounded edges and board pages, this series is designed especially for little hands. With easy-to-read words and a small amount of text, these books are perfect for early readers!